Efisiensi Usaha Ternak Ayam Broiler di Kecamatan Secanggang Kabupaten Langkat - Fadila, Nelly Dewi; Hanisah, Hanisah; Basriwijaya, Kiagus Muhammad Zain (Universitas Medan Area, 2025)
The research aims to analyze the efficiency of the broiler chicken farming business in Secanggang district, langkat regency. The sampling technique was carried out using census techniques with a sample size of 26 people. The data used in this research are primary data and secondary. To determine the efficiency of the broiler chicken business in Secanggang District, langkat Regency, Cobb-Douglas production factor analysis was used. Data processing was carried out using SPSS 25 software. Simultaneously, chicken seeds, starter feed, grower feed, finisher feed and medicines affect the broiler chicken farming business in Secanggang District, Langkat Regency, while partially those that affect the broiler chicken farming business in Secanggang District, Langkat Regency are chicken seeds, grower feed, finisher feed, medicines and those that do not affect are starter feed. Production factors (chicken seeds, starter feed, grower feed, finisher feed and medicines) used in the broiler chicken farming business in Secanggang District, Langkat Regency, seen from the economic side, are still not efficient.